Damage-Associated Molecular Pattern-Triggered Immunity in Plants - Hou, Shuguo; Liu, Zunyong; Shen, Hexi; Wu, Daoji (Frontiers in Plant Science, 2019)
As a universal process in multicellular organisms, including animals and plants, cells usually emit danger signals when suffering from attacks of microbes and herbivores, or physical damage. These signals, termed as damage-associated molecular patterns (DAMPs), mainly include cell wall or extracellular protein fragments, peptides, nucleotides, and amino acids. Once exposed on cell surfaces, DAMPs are detected by plasma membrane-localized receptors of surrounding cells to regulate immune responses against the invading organisms and promote damage repair. DAMPs may also act as long-distance mobile signals to mediate immune and wounding responses systemically. Generation, release, and perception of DAMPs, and signaling events downstream of DAMP perception are all rigorously modulated by plants. These processes integrate together to determine intricate mechanisms of DAMP-triggered immunity in plants. In this review, we present an extensive overview on our current understanding of DAMPs in plant immune system.